Gambaran keparahan karies pada anak usia 6, 9 dan 12 tahun di Kabupaten Pinrang , Sulawesi Selatanmenggunakanindeks PUFA/pufa Overview of severity of dental caries on 6, 9, and 12 years old children in Pinrang Regency, South Sulawesi using PUFA/pufa index - Rini Pratiwi; Ririn Mutmainnah (Journal of Dentomaxillofacial Science, 2013)
Caries remains a major challenge for public health, and is a major problem for children. Based on 2007 Basic HealthResearch, in South Sulawesi, the prevalence of oral health problems of 5-14-year-old children was 42.2% and theprevalence of active caries on children aged 12 years was 39%. This study aims to describe the severity of untreatedcaries at 6, 9 and 12 years old, using pathfinder survey, samples are 6, 9 and 12 years old, respectively 450 children,in three districts of Pinrang, South Sulawesi. Index of PUFA/pufa was used to assess the severity of untreated caries.This index records the involvement of pulp (P/p), ulceration (U/u) of oral mucosa due to tooth fragment, fistula (F/f)and abscess (A/a). The results showed that most found caries involve the pulp exposure both in the permanent (P) anddeciduous (p) on the entire sample. Overall caries prevalence on 6-year-old is 62% with the highest component ofdental caries and there are 8 permanent teeth with caries with pulp involvement. For ages 9 years 65.8% with a 10% permanent dental caries and 12 years old is the highest prevalence of caries in permanent teeth, which is 25.3%. It isconcluded that 9-year-old children in the mixed dental period showed severe caries.